A Formal Representation of the Anodic Voltammetric Response of Polyaniline - Marmisollé, Waldemar Alejandro (2011)
It is presented a formal representation of the oxidation of Polyaniline (Pani) films that allows fitting the experimental voltammetric current-potential response of Pani modified electrodes. The model includes interactions between the redox centers and takes into account both the faradaic and the capacitive current contributions to the total voltammetric response. Although the separation of both contributions is not possible by just voltammetric techniques, the present formalism allows completely characterizing the voltammetric anodic behavior of conducting polymers. Its suitability is proved to represent the current-potential response of Pani films of different thickness in 3.7 M H2SO4 solutions. © 2011 Elsevier B.V. All rights reserved.